2017
DOI: 10.1007/s00432-017-2440-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a-5p (miR-30a) regulates cell motility and EMT by directly targeting oncogenic TM4SF1 in colorectal cancer

Abstract: These results suggest that miR-30a is an important regulator of TM4SF1, VEGF, and E-cadherin for CRC lymph node metastasis, a potential new therapeutic target in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
0
39
0
1
Order By: Relevance
“…Increasing evidence demonstrates that restoration of miR-30a contributes to the suppression of EMT process in various cancers and fibrotic diseases [24, 34, 35], indicating an inhibitory role of miR-30a in EMT. Generally, TGF-β1, Vimentin, E-cadherin and GFAP are considered to be important EMT markers.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates that restoration of miR-30a contributes to the suppression of EMT process in various cancers and fibrotic diseases [24, 34, 35], indicating an inhibitory role of miR-30a in EMT. Generally, TGF-β1, Vimentin, E-cadherin and GFAP are considered to be important EMT markers.…”
Section: Discussionmentioning
confidence: 99%
“…Other experiments showed that miR-483 could inhibit cell proliferation in Polycystic Ovarian Syndrome via Targeting Insulin-Like Growth Factor 1 (IGF1) [17]. Although there are many studies on microRNA and colon cancer, such as mir-30a-5p (miR-30a) regulates cell motility and EMT by targeting TM4SF1 in colorectal cancer [18]. MiR-944 inhibits cell migration and invasion by targeting MACC1 in colorectal cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Recent studies have examined the correlation of TM4SF1 with microRNAs in tumor angiogenesis of various cancers. 35,36 TM4SF1 is reportedly one of the candidate markers of thyroid cancer stem cells; however, its clinical application needs to be studied further. 37 There are no existing scientific studies of TM4SF1 expression in thyroid cancer tissue.…”
Section: F I G U R E 3 Validation Of Microarray-based Gene Expressionmentioning
confidence: 99%